Antropocentrict aspects of korean somantic phraseological units (Journal of Oriental Studies, 2016)
It is known that somatic phraseology – one of the most ancient layers of phraseology, it is directly connected with perception of theworld, its knowledge. In everyone language the somatic phraseology occupies the big role, and in the Korean language too. In giventhe description and the characteristic of somatic phraseological units of the Korean language, and also comparison with the Kazakhlanguage is given to article.